Quadruplex-Interactive Agents as Telomerase Inhibitors: Synthesis of Porphyrins and Structure−Activity Relationship for the Inhibition of Telomerase - Shi, Dong-Fang; Wheelhouse, Richard T; Sun, Daekyu; Hurley, Laurence H (Journal of medicinal chemistry, 2001)
The cationic porphyrin 5,10,15,20-tetra-(N-methyl-4-pyridyl)porphyrin (TMPyP4) binds to quadruplex DNA and is thereby an inhibitor of human telomerase (Wheelhouse et al. J. Am. Chem. Soc. 1998, 120, 3261−3262). Herein the synthesis and telomerase-inhibiting activity of a wide range of analogues of TMPyP4 are reported, from which rules for a structure−activity relationship (SAR) have been discerned:  (1) stacking interactions are critical for telomerase inhibition, (2) positively charged substituents are important but may be interchanged and combined with hydrogen-bonding groups, and (3) substitution is tolerated only on the meso positions of the porphyrin ring, and the bulk of the substituents should be matched to the width of the grooves in which they putatively lie. This SAR is consistent with a model presented for the complexation of TMPyP4 with human telomeric quadruplex DNA.